LUDY TUBYLCZE W RELACJACH LIWIUSZA I POMPEJUSZA TROGUSA/JUSTYNA O WYPRAWIE DO ITALII ALEKSANDRA Z EPIRU - Małgorzata Pawlak (In Gremium. Studies in History, Culture and Politics, 2018)
Alexander of Epirus arrived in Italy in 334/333 BC to support Taranto in fighting the natives. The most comprehensive descriptions of this expedition are found in the works of Livy and Pompeius Trogus (known to us through Justin). The main opponents of Alexander were the Lucanians and Bruttians, against whom he fought and was successful – conquering their cities and defeating the combined Lucanian-Samnite forces in the battle near Paestum. At the same time, he carried out a diplomatic action, remaining in the alliance not only with Greek cities, but also with part of the natives, including the peoples of Puglia (Messapians). Undoubtedly, the indigenous people of Italy played a crucial role in attaining his political goal to create a new balance of power in the southern part of the Apennine Peninsula. This ambitious plan, however, was ruined by the death of the king in a clash near Pandosia.